2009
DOI: 10.1097/scs.0b013e3181bec66e
|View full text |Cite
|
Sign up to set email alerts
|

Otomyiasis by Wohlfahrtia magnifica

Abstract: Myiasis has been defined as the infestation of tissue with dipterous larvae that feed on the host's dead or living tissue. A new clinical report of otomyiasis in a 57-year-old woman caused by Wohlfahrtia magnifica was reported. A review of the English language literature reveals 5 articles on otomyiasis cases caused by W. magnifica. Although it is not a frequent manifestation in otorhinolaryngology, the opportunity of its occurrence always exists. In the treatment, a combination of suctioning and alligator for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…9); an inflamed and swollen auditory canal is a common finding, and in some cases, tympanic membrane perforation can be visualized (369). Imaging studies, such as computed tomography, are indicated to evaluate possible complications other than tympanic membrane perforation, such as the invasion and destruction of the mastoid cavity (8,180,350). Other reported complications are deafness and penetration within the central nervous system with meningitis, where death may occur (350).…”
Section: Cavitary Myiasismentioning
confidence: 99%
See 2 more Smart Citations
“…9); an inflamed and swollen auditory canal is a common finding, and in some cases, tympanic membrane perforation can be visualized (369). Imaging studies, such as computed tomography, are indicated to evaluate possible complications other than tympanic membrane perforation, such as the invasion and destruction of the mastoid cavity (8,180,350). Other reported complications are deafness and penetration within the central nervous system with meningitis, where death may occur (350).…”
Section: Cavitary Myiasismentioning
confidence: 99%
“…The most important species causing aural myiasis are C. hominivorax (232,245,355), W. magnifica (34,100,180,264,341,350), C. bezziana (1,8,134,289), C. megacephala (203), Sarcophaga (6,214,347,353,360), and Parasarcophaga crassipalpis (240).…”
Section: Cavitary Myiasismentioning
confidence: 99%
See 1 more Smart Citation
“…However, dogs have recently acquired an important role as reservoir in the epidemiology of wohlfahrtiosis in Morocco and Hungary ). Human cases of wohlfahrtiosis have been also recently reported in Europe and Asia (Büyükkurt et al 2008;Karaman et al 2009;Tuygun et al 2009;Bayindir et al 2010;Robbins and Khachemoune 2010).…”
Section: Introductionmentioning
confidence: 91%
“…The infestation with fly larvae has a worldwide distribution, however since the flies prefer hot and humid environments, high prevalence rates occur in W. magnifica has been reported as the causative agent of different types of myiasis including orotracheal (12), aural (13), furuncular (14), oral (15), mastoidectomy cavity (16), otomyiasis (17), and cutaneous myiasis (18) in Turkey, in addition to these orbital (19), gingival (20), and urogenital (21) Aural infestations occur frequently in patients with poor personal hygiene, children and also adults with intellectual disabilities (22). In a study recently it was mentioned that aural myiasis is usually observed in children under 10 (3).…”
Section: Cilt 74  Sayı 4  2017mentioning
confidence: 99%